Response of potted tomato (Lycopersicon esculentum) to plant growth-promoting rhiszobacterial inoculants applied singly and in combination - Hechanova, Hamir Chin (2009)
Three bacterial isolates obtained from the rhizosphere of sago palm in Agusan Marsh were tested for their effects on the root and shoot fresh weight, root and shoot dry weight, final shoot length, rate of shoot increase and fruit yield of two tomato cultivars, the open pollinated Super Pope and the hybrid Diamante. Plants grown in sterile soil survived better than those grown in non-sterile soil, which were infested with fungal pathogens. The single inoculum and combination of Rh1-MS-CO, Rh2-MS-CO and Rh3-MS-CO performed poorly against the negative control on the shoot and root fresh weight, final shoot length and rate of shoot increase. However, the effects of the three rhizobacteria were evident on the shoot and root dry weight, fruit yield and number of fruit per plant of tomato. Three is no significant difference between the two cultivars, however, rhizobacteria performed better when inoculated to the Super Pope in terms of final shoot length, rate of shoot increase and shoot fresh weight. The treatments containing either Rh1-MS-CO, Rh2-MS-CO or Rh3-MS-CO or the combination of these three contributed to a high fruit yield. The treatment containing Rh1-MS-CO contributed to a higher number of fruit. The growth promotion via root and shoot dry weight, fruit yield and total number of fruit per treatment show the potential of the three rhizobacterial strains as PGPR